National Sample Survey Organisation Thirty Eighth Round (January-December 1983) Report on the Third Quinquennial Survey on Employment and Unemployment Survey Results - Jammu and Kashmir - Planning Commission (Planning Commission, 1989)
The details of sampling design, survey coverage, estimation procedure and salient features of the conceptual frame and. data collection procedure adopted in the survey are given in the Report containing the all—India results (Report No.341). A brief summary of the scope and. coverage of the survey, the concepts, definitions, etc., is given below. Section 2 gives some key results with the corresponding results fort all-India.
Department of Statistics Government of India